Latent Profile Analysis of a Syndemic of Vulnerability Factors on Incident Sexually Transmitted Infection in a Cohort of Black Men Who Have Sex With Men Only and Black Men Who Have Sex With Men and Women in the HIV Prevention Trials Network 061 Study. Issue 9 (September 2020) - Dyer, Typhanye V.; Turpin, Rodman E.; Stall, Ron; Khan, Maria R.; Nelson, LaRon E.; Brewer, Russell; Friedman, M. Reuel; Mimiaga, Matther J.; Cook, Robert L.; O'Cleirigh, Conall; Mayer, Kenneth H.
Abstract : Background: Sexually transmitted infections (STIs) are important public health concerns among black men who have sex with men only (BMSMO), as well as those who have sex with both men and women (BMSMW). Sexually transmitted infections also increase risk of acquiring and HIV, which is also a critical concern. Compared with BMSMO, research shows that BMSMW experience elevated levels of HIV/STI vulnerability factors occurring at the intrapersonal, interpersonal, and social/structural levels. These factors may work independently, increasing one's risk of engaging in high-risk sexual behaviors, but often work in a synergistic and reinforcing manner. The synergism and reinforcement of any combination of these factors are known as a syndemic, which increases HIV/STI risk. Methods: Data from the HIV Prevention Trials Network (HPTN) 061 study (n = 799) was used to conduct a latent profile analysis to identify unique combinations of risk factors that may form a syndemic and that may vary between BMSMO and BMSMW. We hypothesized that the convergence of syndemic factors would differ between groups and predict sexual risk and subsequent incident STI. Results: For BMSMO who had a high sexual risk profile, the syndemic factors characterizing this group included perceived racism, incarceration, intimate partner violence, depression, and binge drinking. For BMSMW with a high sexual risk profile, the syndemic factors that characterized this group were incarceration, depression, and binge drinking. Conclusions: The current analysis highlights syndemic profiles that differentiated BMSMO and BMSMW from one another and supports the need for tailored interventions that address specific syndemic factors for both subpopulations of black men who have sex with men. Abstract : The current study highlights syndemic profiles that differentiated black men who have sex with men only and black men who have sex with both men and women from one another and support the need for tailored interventions.Supplemental digital content is available in the text.